Peningkatan Kemampuan Anak Mengenal Bentuk Geometri Melalui Media Balok di TK Ar-Raudah Padang - Resy Yanti; Asdi Wirman (Jurnal Halaqah, 2020)
Geometry is one branch of mathematics that aims to develop the conjugative aspects of children. In accordance with Permendikbud Number 146 that children are able to convey about what and how objects around them are known (names, colors, shapes, sizes, patterns, properties, sounds, textures, functions, and other features) through various works. The purpose of this study is to improve children's ability to recognize geometric shapes through “Balok Media”. This type of research is Classroom Action Research (CAR). The subjects in this study were group A with 10 people. The study was conducted in two cycles in collecting data is observation and documentation and research results are processed by percentage techniques. The results showed that in cycle I there were three meetings with a percentage of 36%. In cycle II there were as many as three meetings with a percentage of 84%. It was concluded that recognizing geometric shapes can improve children's abilities in Taman Kanak-kanak Ar Raudah Padang.